2010
DOI: 10.1243/09544070jauto1581
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Emissions of a Turbocharged, High-Pressure Common Rail Diesel Engine Operating on Biodiesel/Diesel Blends

Abstract: The effect of biodiesel addition to diesel on engine performance, combustion, and emissions were studied in a turbocharged, high-pressure common rail diesel engine. Biodiesel/diesel blends with different biodiesel fractions were used and compared with neat biodiesel and diesel at different engine loads and speeds. The results show that the brake thermal efficiency increases slightly as biodiesel is added to diesel. Exhaust gas temperature is not significantly affected at low engine speeds and decreases gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…It was found that different oil sources for biodiesel lead to different NO x emission results, which include increase and decrease of these emissions. Wang et al [30] report improvements in combustion and energetic efficiency for B20 and B40 blends when compared with diesel (B0). It is concluded that the differences in the heat released from combustion and the lower temperature for low loads also induce a small reduction in NO x emissions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that different oil sources for biodiesel lead to different NO x emission results, which include increase and decrease of these emissions. Wang et al [30] report improvements in combustion and energetic efficiency for B20 and B40 blends when compared with diesel (B0). It is concluded that the differences in the heat released from combustion and the lower temperature for low loads also induce a small reduction in NO x emissions.…”
Section: Introductionmentioning
confidence: 99%
“…This is considered to be an optimized blend. Fig: 9 indicate the variation of SFC with injection pressure, in which B20 providing greater result [15]. When the injection pressure is increased up to a certain level the thermal efficiency also increased.…”
Section: A Optimized Blendmentioning
confidence: 94%
“…1-4 dioxin, as an additive in TBC engines reduces smoke density with slight increase in brake thermal efficiency and NO x with a drop in fuel economy [7]. Reduced ignition delay reduces combustion temperature which aids in reducing NO x emissions since higher combustion temperature is the primary source for NO x to increase [8]. The use of cetane improvers is an alternative way to reduce the NO x emissions which can be done by reducing ignition delay in diesel engines [9].…”
Section: Introductionmentioning
confidence: 99%